British counterinsurgency in Brunei and Sarawak, 1962–1963: developing best practices in the shadow of Malaya. (3rd July 2016) - Shaw, Alexander Nicholas
Abstract: This paper uses recently-released material from the 'migrated archives' to provide an original counterinsurgency analysis of the TNKU revolt in Brunei and Sarawak from December 1962 to May 1963. It argues that, despite a failure to act upon intelligence predicting the outbreak of insurgency, Britain developed a highly effective counterinsurgency organisation. These records also indicate that decision-makers drew inspiration from the Malayan Emergency to inform success in Brunei. Although Malaya has been challenged as a counterinsurgency paradigm, the Brunei operations show the utility of striking a balance between inappropriately copying from past campaigns and developing best practices applicable to the unique environment of Borneo. In turn, the evolution of effective operational practices in Brunei informed their successful application to the subsequent Indonesian Confrontation.